Gender roles, sex and the expression of driving anger. (September 2017) - Sullman, M.J.M.; Paxion, J.; Stephens, A.N.
Highlights: CFA supported the four-factor structure of the 25-item Driving Anger Expression Inventory in a French sample. Use of the vehicle to express anger was related to almost all crash-related conditions. Higher femininity, but not sex, was predictive of adaptive/constructive behaviour. Higher masculinity was predictive of engagement in more aggressive forms of anger expression. An individual's sex-role appears to be more useful than biological sex to understand the relationship with driving anger. Abstract: The present study investigated the validity of the 25-item Driving Anger Expression Inventory (DAX) as well as the role of sex and gender-roles in relation to the expression of driving anger in a sample of 378 French drivers (males = 38%, M = 32.9 years old). Confirmatory Factor Analysis supported the four-factor structure of the 25-item DAX (Adaptive/Constructive Expression; Use of the Vehicle to Express Anger; Verbal Aggressive Expression and Personal Physical Aggressive Expression) and two of the three aggressive factors were found to have significant positive relationships with driving anger, while adaptive/constructive expression was negatively related to driving anger. Use of the vehicle to express anger was not significantly related to crash involvement, but was significantly related to all other crash-related conditions (traffic tickets, loss of concentration, loss of control of the vehicle, near crash). The presence of feminine traits, but not sex, was predictive of adaptive/constructive behaviours, while masculine traits predicted more frequent verbal aggressive expression, use of the vehicle to express anger, personal physical aggressive expression and total aggressive expression. This finding may account for the inconsistent relationship found between driving anger and sex in previous research. This research also found that the 25-item DAX is a valid tool to measure the expression of driving anger and that the endorsement of masculine traits are related to more aggressive forms of driving anger expression.